XML-Coursebuilder, V. 1.0 XML and XSLT format course modules into a comprehensive presentation. - Miller, Mark (XML journal :the ultimate enterprise resource.)
As a corporate trainer of Internet technologies. I've often run into situations where a company will look at a set of courses within a curriculum and say, "I want Section 2 of that course, followed by Section 4 from this other course, and then we've got a realworld project we would like you to review with the class at the conclusion of the course."